SOSIALISASI BAHAYA NARKOBA SEBAGAI UPAYA PENCEGAHAN DINI DI KALANGAN SISWA SMP NEGRI 1 DAMPAL SELATAN - Al Amin; Warda Said (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
Drug abuse among adolescents is a serious threat to health and the future of the young generation. To address this issue, students of the KKN Program from Madako University conducted a Socialization on the Dangers of Drugs at SMP Negeri 1 Dampal Selatan on June 23, 2025. The program aimed to increase students’ understanding of drug types, harmful effects, and legal consequences related to drug abuse. The methods applied included lectures, discussions, question-and-answer sessions, educational video screenings, and the distribution of posters and leaflets. A total of 78 students actively participated in the program. The evaluation results indicated that more than 85% of the participants gained new knowledge, while the rest stated that their prior understanding was strengthened. This socialization program proved effective in raising awareness and promoting preventive attitudes among students to stay away from drugs. Therefore, it contributes to creating a healthy, productive, and drug-free school environment.